Anomalous Left Circumflex Artery: Insights and Challenges in Primary Percutaneous Intervention (PCI) - Mathew, Cinosh (Medical Science: Trends and Innovations Vol. 3, 2025)
Congenital coronary anomalies are rarely found in patients undergoing diagnostic coronary angiography (0.2% - 1%). These anomalies cause difficulty in the early identification of the culprit anomalous artery and complicate the engagement of the affected vessel especially in a Primary percutaneous coronary intervention (PCI) when time is of the essence and rapid reperfusion is warranted. This case report discusses a 56-year-old male patient who presented with an Acute Inferior Wall Myocardial Infarction. While undergoing a diagnostic coronary angiogram, an occluded left circumflex artery (LCx) was discovered, which arose anomalously from the right coronary ostium. Primary percutaneous coronary intervention (PCI) of the LCx could not be performed using standard guide catheters, necessitating a specialized multipurpose guide catheter with balloon support. This case underscores the importance of understanding coronary architecture, the anomalous origins of coronary arteries, and the necessity for selecting appropriate guiding catheters and coronary wires.